A game Pareto complete analysis in n-dimensions: a general applicative study case - Carfì, David (Journal of Mathematical Economics and Finance, 2017)
The study proposed here considers an applicable game model, in a specific non-linear interfering scenario, with n possible interacting elements. We find the Pareto maximal boundary by using the Carfì’s payoff analysis method for differentiable games. The core section of the paper studies the game by finding the critical zone of the game in its Cartesian form. At this aim, we need to prove an intricate theorem and a technical lemma about the Jacobian determinant of the examined n-game.